Pengaruh Kualitas Pelayanan Publik Terhadap Kepuasan Masyarakat di Kantor Kecamatan Sukarami Kota Palembang - Syafebri, Arrahman; Pangestu, Aji (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2025)
This research stems from the increasing demands of citizens for higher-quality public services at the sub-district level, with Sukarami Sub-district in Palembang City functioning as the primary provider of administrative and licensing services. This research underlines the significance of examining the impact of service quality dimensions, including tangibility, reliability, responsiveness, assurance, and empathy, on citizen satisfaction. The main objective is to analyze the extent to which each dimension contributes to overall satisfaction. The research adopted a quantitative approach through a survey design. A five-point Likert scale instrument was employed to gather information from 100 respondents who were chosen through the use of stratified random sampling. The results were analyzed descriptively and supported by instrument reliability testing. The results indicate that citizen satisfaction is categorized as moderate, with a mean score of 3.26. Among the service quality dimensions, responsiveness scored the lowest (2.86), whereas tangibility received a higher score (3.07), reflecting differences in citizens’ perceptions of service provision. The relatively low reliability coefficient suggests that further refinement of the measurement instrument is required. Theoretically, the study reinforces the public service quality model in the local governance context. Practically, it provides recommendations for improving responsiveness and reliability through staff capacity building, streamlined procedures, and the adoption of digital services to enhance sustainable citizen satisfaction.